CRISPR-CAS9 Applications In Gene Editing For Rare Genetic Disorders - Minom Appun Gam (South Eastern European Journal of Public Health, 2025)
CRISPR-Cas9 gene-editing technology has emerged as a groundbreaking tool in modern biotechnology, revolutionizing the treatment landscape for rare genetic disorders. This research article explores the mechanisms and applications of CRISPR-Cas9 in addressing rare monogenic and polygenic diseases, such as cystic fibrosis, Duchenne muscular dystrophy, and sickle cell anemia. The paper highlights key advancements, delivery methods, ethical considerations, and clinical trials while discussing the potential for permanent cures through precise genomic correction. Challenges such as off-target effects, immune responses, and regulatory hurdles are also addressed. Overall, CRISPR-Cas9 holds immense promise in transforming the management of rare genetic disorders and bringing hope to patients with limited therapeutic options.